Ammonia-free latex medical examination gloves and preparation method thereof

By adding vinyl silane coupling agent, isoprene and styrene-copolymerized diatomaceous earth to copolymerized by ammonia-free latex medical examination gloves, the problem of insufficient wear resistance and tensile strength of existing gloves is solved, and the problem of insufficient wear resistance and tensile strength of existing gloves is achieved. Higher wear resistance and tensile strength while reducing environmental and operator impact.

CN118290828BActive Publication Date: 2025-02-07YUNNAN SENJIE MEDICAL LATEX EQUIP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410431999.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-02-07
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

The existing ammonia-free latex medical examination gloves have shortcomings in wear resistance and tensile strength, and have a great impact on the environment and operators during use.

Method used

The wear resistance and tensile strength of medical examination gloves are significantly improved by adding vinyl silane coupling agent, isoprene and styrene to the ammonia-free concentrated natural latex.

Benefits of technology

It significantly improves the wear resistance and tensile strength of ammonia-free latex medical examination gloves, reduces the impact on the environment and operators, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004785921020000081
    Figure BDA0004785921020000081
Patent Text Reader

Abstract

The present invention relates to the technical field of medical gloves, in particular to an ammonia-free latex medical examination glove and a preparation method thereof, wherein the raw materials include by weight: 1000 parts of 60wt% ammonia-free concentrated natural latex, 1-10 parts of modified diatomite, 5-20 parts of potassium hydroxide, 5-20 parts of sulfur powder, 5-15 parts of zinc oxide, 5-15 parts of accelerator ZDC, 10-20 parts of antioxidant BHT, and 1-3 parts of surfactant peregal O; the preparation method of the modified diatomite includes: modifying the diatomite with a vinyl silane coupling agent, and then adding isoprene and styrene for copolymerization modification. The present invention significantly improves the wear resistance and tensile strength of the ammonia-free latex medical examination gloves through the self-made modified diatomite, while reducing the influence of environmental odor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of medical gloves, and in particular to an ammonia-free latex medical examination glove and a preparation method thereof. Background Art

[0002] Medical examination gloves have a barrier protection effect, which can well protect the safety of users and are widely used in people's production and life. At present, natural concentrated latex is generally used as the raw material for the production of medical examination gloves. Natural concentrated latex is made by separating excess water and impurities from latex particles through high-speed centrifugation of fresh latex. In order to prevent the deterioration of natural latex, it is usually necessary to add substances that inhibit bacteria and enzyme activity. Among them, ammonia is the most widely used preservative. When 0.05%-0.1% is added, the latex can be stored for 16 hours without deterioration. When 0.25% is added, the latex can be stored for seven days without deterioration. When the amount added to the latex reaches 0.7%, the latex can be stored for one year without deterioration. Due to the special smell of ammonia produced by the volatility of ammonia, raw latex or compounded latex preserved with ammonia causes pollution to the environment and affects the health of operators during the application process. At present, low-ammonia and ammonia-free preservatives have been gradually developed, such as the HY preservation system and the BCT-2 preservation system.

[0003] Patent application CN110054813B discloses the application of low-ammonia or ammonia-free latex in household rubber gloves, including 100 natural raw latex, 0.1-1.0 casein, 0-1.5 potassium hydroxide, 1-7 mixed dispersions, 0.1-0.4 surfactants, 1-10 fillers, 0-3 additives, and the filler is nano calcium carbonate. Although it has high tensile and tear strength, it still needs to be improved, and its wear resistance has not been significantly improved.

[0004] Therefore, it is necessary to provide an improved ammonia-free latex medical examination glove and a preparation method thereof to obtain a medical examination glove with good wear resistance and high tensile strength. Summary of the invention

[0005] The object of the present invention is to provide an ammonia-free latex medical examination glove and a preparation method thereof, and to significantly improve the wear resistance and tensile strength of the ammonia-free latex medical examination glove by adding a vinyl silane coupling agent and diatomaceous earth modified by copolymerization of isoprene and styrene.

[0006] To achieve the above object, the present invention provides an ammonia-free latex medical examination glove, wherein the raw materials include, by weight: 1000 parts of 60wt% ammonia-free concentrated natural latex, 1-10 parts of modified diatomaceous earth, 5-20 parts of potassium hydroxide, 5-20 parts of sulfur powder, 5-15 parts of zinc oxide, 5-15 parts of accelerator ZDC, 10-20 parts of antioxidant BHT, and 1-3 parts of surfactant peregrin O;

[0007] The preparation method of the modified diatomite comprises: modifying the diatomite by using a vinyl silane coupling agent, and then adding isoprene and styrene for copolymerization modification.

[0008] Furthermore, the molar ratio of isoprene to styrene is (2-5):1.

[0009] Furthermore, the added amount of the vinyl silane coupling agent is 10-25% of the mass of the diatomaceous earth, and the mass ratio of the styrene to the vinyl silane coupling agent is (3-20):1.

[0010] Furthermore, the polymerization degree of isoprene is 10-100.

[0011] Furthermore, the polymerization degree of isoprene is 30-50, and the molar ratio of isoprene to styrene is (3-4):1.

[0012] Furthermore, the preparation method of the modified diatomite includes: adding diatomite with a particle size of 0.1 to 1 μm to a mixed solvent of ethanol and water, then adding vinyltrimethoxysilane, reacting at 40 to 80° C. for 1 to 3 hours, and then centrifuging to obtain diatomite modified by a silane coupling agent; dispersing the diatomite modified by a silane coupling agent in chloroform, then adding styrene and an initiator, reacting at 80 to 110° C. for 1 to 3 hours, and then adding isoprene, reacting at 80 to 110° C. for 1 to 5 hours to obtain modified diatomite.

[0013] Furthermore, the ammonia-free concentrated natural latex is prepared by centrifugation and concentration of natural fresh latex; the natural fresh latex is preserved by a bactericide and a stabilizer before centrifugation and concentration; the bactericide is a propylene glycol derivative; the ammonia-free concentrated natural latex is preserved by an ammonia-free preservation system, and the ammonia-free preservation system is a HY preservation system.

[0014] Furthermore, the composition comprises, by weight: 1000 parts of 60wt% ammonia-free concentrated natural rubber latex, 3-6 parts of modified diatomaceous earth, 10-20 parts of potassium hydroxide, 10-20 parts of sulfur powder, 10-15 parts of zinc oxide, 10-15 parts of accelerator ZDC, 10-20 parts of antioxidant BHT, and 1-3 parts of surfactant Periga O.

[0015] The present invention also provides a method for preparing the ammonia-free latex medical examination gloves described in any one of the above items, comprising: impregnating raw latex into a mold at 25-30° C., drying with hot air at 60-110° C.; then drying and vulcanizing at 90-110° C. for 15-30 minutes to obtain the ammonia-free latex medical examination gloves;

[0016] The raw latex is the raw material of the ammonia-free latex medical examination gloves described in any one of the above items.

[0017] Furthermore, the mold is cleaned before use, and the cleaning steps include: preheating with hot water at 85-95°C, dipping in a coagulant after drying, and then drying at 85-100°C for standby use.

[0018] The beneficial effects of the present invention are as follows:

[0019] The ammonia-free latex medical examination gloves provided by the present invention can effectively improve the wear resistance and tensile strength of the latex gloves by adding a vinyl silane coupling agent and diatomaceous earth modified by copolymerization of isoprene and styrene to the ammonia-free concentrated natural latex. The ammonia-free natural concentrated latex is more conducive to the production of latex gloves, saves costs, and reduces the impact of environmental odor. At the same time, the cut resistance, tear resistance and puncture resistance are also excellent. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The ammonia-free latex medical examination gloves provided by the present invention include raw materials in parts by weight: 1000 parts of 60wt% ammonia-free concentrated natural latex, 1-10 parts of modified diatomaceous earth, 5-20 parts of potassium hydroxide, 5-20 parts of sulfur powder, 5-15 parts of zinc oxide, 5-15 parts of accelerator ZDC, 10-20 parts of antioxidant BHT, and 1-3 parts of surfactant peregrin O;

[0022] The preparation method of the modified diatomite comprises: modifying the diatomite by using a vinyl silane coupling agent, and then adding isoprene and styrene for copolymerization modification.

[0023] The siloxane of the vinyl silane coupling agent is hydrolyzed and then condensed with the hydroxyl groups on the surface of the diatomaceous earth to achieve grafting. Then, isoprene and styrene are added to extend the molecular chain through free radical polymers. The modified diatomaceous earth thus obtained has improved compatibility with natural rubber latex and is easy to disperse evenly. On the other hand, isoprene can participate in cross-linking during the vulcanization process to improve the strength and wear resistance of the rubber. The presence of phenyl can also help improve the strength and wear resistance.

[0024] Preferably, the raw materials include, by weight: 1000 parts of 60wt% ammonia-free concentrated natural rubber latex, 3-8 parts of modified diatomaceous earth, 10-15 parts of potassium hydroxide, 10-15 parts of sulfur powder, 6-12 parts of zinc oxide, 8-15 parts of accelerator ZDC (zinc diethyldithiocarbamate), 10-20 parts of antioxidant BHT (2,6-di-tert-butyl-p-cresol), and 1-3 parts of surfactant Periga O (polyoxyethylene fatty alcohol ether).

[0025] Preferably, the molar ratio of isoprene to styrene is (2-5): 1, and the molar ratio of isoprene to styrene is (3-4): 1, preferably 3: 1. By adjusting the ratio of the two, the copolymer chain segment can be adjusted, and then the cross-linking structure of the modified diatomaceous earth and natural rubber molecular chain can be adjusted, so as to obtain ammonia-free latex medical examination gloves with better comprehensive performance.

[0026] Preferably, the amount of the vinyl silane coupling agent added is 10-25% of the mass of the diatomite, preferably 15-20%. The vinyl silane coupling agent is vinyl trimethoxysilane and / or methyl vinyl dimethoxysilane. Preferably, the molar ratio of vinyl trimethoxysilane and methyl vinyl dimethoxysilane is 3:1. This is because vinyl trimethoxysilane has three silanol groups after hydrolysis, and can form a cross-linked network structure when condensed with the silanol groups of diatomite. This cross-linked network structure helps to improve the strength of the rubber, but it is not suitable for excessive cross-linking. Therefore, it is adjusted by an appropriate amount of methyl vinyl dimethoxysilane to obtain a modified diatomite with better reinforcement effect.

[0027] The mass ratio of styrene to vinyl silane coupling agent is (3-20):1, preferably (10-15):1.

[0028] Preferably, the degree of polymerization of the isoprene is 10 to 100. Preferably, the degree of polymerization of the isoprene is 30 to 50.

[0029] Preferably, the preparation method of the modified diatomite comprises: adding diatomite with a particle size of 0.1 to 1 μm to a mixed solvent of ethanol and water, then adding vinyltrimethoxysilane, reacting at 40 to 80° C. for 1 to 3 hours, and then centrifuging to obtain diatomite modified by a silane coupling agent; dispersing the diatomite modified by a silane coupling agent in chloroform, then adding styrene and an initiator, reacting at 80 to 110° C. for 1 to 3 hours, and then adding isoprene, reacting at 80 to 110° C. for 1 to 5 hours to obtain modified diatomite.

[0030] In the present invention, styrene is preferably added first to polymerize it with the vinyl of the silane coupling agent, and then isoprene is added for copolymerization. The modified diatomaceous earth obtained in this way has the diatomaceous earth-silane coupling agent-polystyrene chain segments on the same side of the isoprene after the isoprene participates in cross-linking, and has better regularity, which helps to improve processability and strength.

[0031] Furthermore, the ammonia-free concentrated natural latex is prepared by centrifugation and concentration of natural fresh latex; the natural fresh latex is preserved by a bactericide and a stabilizer before centrifugation and concentration; the bactericide is a propylene glycol derivative, the stabilizer is sodium carbonate, and the ammonia-free concentrated natural latex is preserved by an ammonia-free preservation system, which is a HY preservation system.

[0032] The bactericide is 0.12% of the weight of natural fresh latex, and the stabilizer is 0.1% of the weight of natural fresh latex; the HY preservation system is composed of HY (1,3,5-trimethylhexahydro-s-triazine) 0.3%, SDS 0.2%, and KOH 0.1% (all referring to the weight relative to concentrated natural latex).

[0033] The present invention also provides a method for preparing the ammonia-free latex medical examination gloves described in any one of the above items, comprising impregnating raw latex into a mold at 25-30° C. and drying with hot air at 60-110° C.; then drying and vulcanizing at 90-110° C. for 15-30 minutes to obtain the ammonia-free latex medical examination gloves; the raw latex is the raw material of the ammonia-free latex medical examination gloves described in any one of the above items.

[0034] The mold is cleaned before use, and the cleaning steps include: preheating with hot water at 85-95°C, soaking in a coagulant after drying, and then drying at 85-100°C for standby use.

[0035] Example 1

[0036] A kind of ammonia-free latex medical examination gloves, prepare the raw latex: 1000 parts of 60wt% ammonia-free concentrated natural latex, 5 parts of modified diatomaceous earth, 15 parts of potassium hydroxide, 12 parts of sulfur powder, 9 parts of zinc oxide, 10 parts of accelerator ZDC, 12 parts of antioxidant BHT, and 2 parts of surfactant perchlorate O.

[0037] Low ammonia concentrated natural latex is obtained by preserving natural fresh latex with fungicide and stabilizer, then concentrating by centrifugation to a solid content of about 60%, and then preserving without ammonia through HY preservation system. The fungicide is 0.12% of the weight of natural fresh latex, and the stabilizer is 0.1% of the weight of natural fresh latex. The fungicide is composed of equal weights of 2-(2-fluoro-6-nitrophenyl)-1,3-propanediol, kason and sodium tripolyphosphate; the stabilizer is sodium carbonate. The HY preservation system is composed of HY (1,3,5-trimethylhexahydro-s-triazine) 0.3%, SDS 0.2%, KOH 0.1% (all refer to the weight relative to the concentrated natural latex).

[0038] The preparation method of modified diatomite comprises: adding diatomite with an average particle size of about 0.5 μm into a mixed solvent of ethanol and water (volume ratio of 1:1), then adding vinyl trimethoxy silane (the addition amount is 20% of the mass of the diatomite), and reacting at 60°C for 2 hours; then centrifuging to obtain diatomite modified by a silane coupling agent; dispersing the diatomite modified by a silane coupling agent in chloroform, then adding styrene (the addition amount is 15 times the mass of the vinyl trimethoxy silane) and an initiator benzoyl peroxide, reacting at 90°C for 2 hours, then adding isoprene (the molar ratio with styrene is 3:1) and benzoyl peroxide, and reacting at 90°C for 4 hours to obtain modified diatomite.

[0039] The method for preparing ammonia-free latex medical examination gloves comprises the following steps:

[0040] The raw latex was impregnated into the mold at 30°C, and dried with hot air at 90°C for 1 hour; then dried and vulcanized at 100°C for 20 minutes to obtain ammonia-free latex medical examination gloves.

[0041] Example 2

[0042] The difference from Example 1 is that the preparation method of modified diatomite includes: adding diatomite with an average particle size of about 0.5 μm to a mixed solvent of ethanol and water (volume ratio of 1:1), then adding vinyl trimethoxy silane (the addition amount is 20% of the mass of the diatomite), and reacting at 60°C for 2 hours; then centrifuging to obtain diatomite modified by a silane coupling agent; dispersing the diatomite modified by a silane coupling agent in chloroform, then adding isoprene (the same amount as in Example 1) and benzoyl peroxide, reacting at 90°C for 4 hours, and then adding styrene (the addition amount is 15 times the mass of vinyl trimethoxy silane) and initiator benzoyl peroxide, reacting at 90°C for 2 hours to obtain modified diatomite. The rest is the same as in Example 1 and will not be repeated.

[0043] Example 3

[0044] The difference from Example 1 is that the preparation method of modified diatomite includes: adding diatomite with an average particle size of about 0.5 μm to a mixed solvent of ethanol and water (volume ratio of 1:1), then adding vinyl trimethoxysilane and methyl vinyl dimethoxysilane in a mass ratio of 3:1 (the total addition amount is 20% of the mass of diatomite), and reacting at 60°C for 2 hours; then centrifuging to obtain diatomite modified by a silane coupling agent; dispersing the diatomite modified by a silane coupling agent in chloroform, then adding styrene (the addition amount is 15 times the mass of vinyl trimethoxysilane) and initiator benzoyl peroxide, reacting at 90°C for 2 hours, then adding isoprene (with a molar ratio of 3:1 to styrene) and benzoyl peroxide, and reacting at 90°C for 4 hours to obtain modified diatomite. The rest is the same as Example 1 and will not be repeated.

[0045] Example 4

[0046] The difference from Example 1 is that the molar ratio of isoprene to styrene is 5:1. The rest is the same as Example 1 and will not be described in detail.

[0047] Example 5

[0048] The difference from Example 1 is that the amount of styrene added is 5 times the mass of vinyltrimethoxysilane. The rest is the same as Example 1 and will not be described in detail.

[0049] Example 6

[0050] The difference from Example 1 is that the amount of modified diatomaceous earth added is 1 part. The rest is the same as Example 1 and will not be described in detail.

[0051] Example 7

[0052] The difference from Example 1 is that the amount of modified diatomaceous earth added is 10 parts. The rest is the same as Example 1 and will not be described in detail.

[0053] Comparative Example 1

[0054] The difference from Example 1 is that the diatomaceous earth is not modified. The rest is the same as Example 1 and will not be described in detail.

[0055] Comparative Example 2

[0056] The difference from Example 1 is that the preparation method of modified diatomite includes: adding diatomite with an average particle size of about 0.5 μm to a mixed solvent of ethanol and water (volume ratio of 1:1), then adding vinyl trimethoxysilane (the addition amount is 20% of the mass of diatomite), reacting at 60° C. for 2 hours; and then centrifuging to obtain diatomite modified by a silane coupling agent. The rest is the same as Example 1 and will not be repeated.

[0057] Comparative Example 3

[0058] The difference from Example 1 is that the preparation method of modified diatomite includes: adding diatomite with an average particle size of about 0.5 μm to a mixed solvent of ethanol and water (volume ratio of 1:1), then adding vinyl trimethoxy silane (the addition amount is 20% of the mass of diatomite), reacting at 60°C for 2 hours; then centrifuging to obtain diatomite modified by a silane coupling agent. The diatomite modified by a silane coupling agent is dispersed in chloroform, and then styrene (the addition amount is 15 times the mass of vinyl trimethoxy silane) and an initiator benzoyl peroxide are added, and reacting at 90°C for 2 hours to obtain modified diatomite. The rest is the same as Example 1 and will not be repeated.

[0059] Test method: Wear resistance is based on the test standard GB / T9867-2008, method A; tensile strength is based on the test standard GB / T528-2009.

[0060] Table 1 Performance test results of embodiments and comparative examples

[0061]

[0062] As can be seen from Table 1, the order of adding styrene and isoprene has a certain influence on the performance, and the effect is better when isoprene is grafted at the chain end. When vinyltrimethoxysilane and methylvinyldimethoxysilane are used at the same time, the effect is better. When the amount of styrene and isoprene is too small, the wear resistance and strength are reduced. When the diatomaceous earth is not modified, the wear resistance and tensile strength are significantly reduced. This is because the unmodified diatomaceous earth has poor dispersibility and cannot combine with styrene and isoprene molecular chains to synergistically improve the comprehensive performance. When only silane coupling agent is used for modification, the wear resistance and tensile strength are improved, which is attributed to the improvement in dispersibility. When styrene is further copolymerized and grafted, the wear resistance and tensile strength are further improved, but the degree of improvement is limited.

[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ammonia-free latex medical examination glove, characterized in that: The raw materials include by weight: 1000 parts of 60wt% ammonia-free concentrated natural rubber latex, 1-10 parts of modified diatomaceous earth, 5-20 parts of potassium hydroxide, 5-20 parts of sulfur powder, 5-15 parts of zinc oxide, 5-15 parts of accelerator ZDC, 10-20 parts of antioxidant BHT, and 1-3 parts of surfactant Periga O; The preparation method of the modified diatomite comprises: modifying the diatomite by using a vinyl silane coupling agent, and then adding isoprene and styrene for copolymerization modification.

2. The ammonia-free latex medical examination gloves according to claim 1, characterized in that: The molar ratio of isoprene to styrene is (2-5):

1.

3. The ammonia-free latex medical examination gloves according to claim 2, characterized in that: The polymerization degree of the isoprene is 10-100.

4. The ammonia-free latex medical examination gloves according to claim 3, characterized in that: The polymerization degree of the isoprene is 30-50, and the molar ratio of the isoprene to styrene is (3-4):

1.

5. The ammonia-free latex medical examination gloves according to claim 1, characterized in that: The added amount of the vinyl silane coupling agent is 10-25% of the mass of the diatomaceous earth, and the mass ratio of the styrene to the vinyl silane coupling agent is (3-20):

1.

6. The ammonia-free latex medical examination gloves according to any one of claims 1 to 5, characterized in that: The preparation method of the modified diatomite comprises: adding diatomite with a particle size of 0.1 to 1 μm into a mixed solvent of ethanol and water, then adding vinyl trimethoxy silane, reacting at 40 to 80° C. for 1 to 3 hours, and then centrifuging to obtain diatomite modified by a silane coupling agent; dispersing the diatomite modified by a silane coupling agent in chloroform, then adding styrene and an initiator, reacting at 80 to 110° C. for 1 to 3 hours, and then adding isoprene, reacting at 80 to 110° C. for 1 to 5 hours to obtain the modified diatomite.

7. The ammonia-free latex medical examination gloves according to any one of claims 1 to 5, characterized in that: The ammonia-free concentrated natural latex is prepared by centrifugation and concentration of natural fresh latex; the natural fresh latex is preserved by a bactericide and a stabilizer before centrifugation and concentration; the bactericide is a propylene glycol derivative; the ammonia-free concentrated natural latex is preserved by an ammonia-free preservation system, and the ammonia-free preservation system is a HY preservation system.

8. The ammonia-free latex medical examination gloves according to any one of claims 1 to 5, characterized in that: The invention comprises, by weight: 1000 parts of 60wt% ammonia-free concentrated natural rubber latex, 3-6 parts of modified diatomaceous earth, 10-20 parts of potassium hydroxide, 10-20 parts of sulfur powder, 10-15 parts of zinc oxide, 10-15 parts of accelerator ZDC, 10-20 parts of antioxidant BHT and 1-3 parts of surfactant Periga O.

9. A method for preparing the ammonia-free latex medical examination gloves according to any one of claims 1 to 8, characterized in that: Dip raw latex into the mold at 25-30°C and dry with hot air at 60-110°C; Then, the process is dried and vulcanized at 90-110° C. for 15-30 minutes to obtain ammonia-free latex medical examination gloves; the raw latex is the raw material of the ammonia-free latex medical examination gloves according to any one of claims 1 to 8.

10. The method for preparing ammonia-free latex medical examination gloves according to claim 9, characterized in that: The mold is cleaned before use, and the cleaning steps include: preheating with hot water at 85-95°C, soaking in a coagulant after drying, and then drying at 85-100°C for standby use.

Citation Information

Patent Citations

  • Application of low-ammonia or ammonia-free latex in household rubber gloves

    CN110054813B

  • PVC (Polyvinyl Chloride) thermoplastic elastomer cable material and preparation method thereof

    CN103881261A

  • Application of low-ammonia or ammonia-free latex in domestic rubber gloves

    CN110054813A